Greek Tragedy. - Rabinowitz, Nancy Sorkin (Blackwell introductions to the classical world., 2008)
Greek Tragedy sets ancient tragedy into its original theatrical, political and ritual context and applies modern critical approaches to understanding why tragedy continues to interest modern audiences.:.; An engaging introduction to Greek tragedy, its history, and its reception in the contemporary world with suggested readings for further study.; Examines tragedys relationship to democracy, religion, and myth.; Explores contemporary approaches to scholarship, including structuralist, psychoanalytic, and feminist theory.; Provides a thorough examination of contemporary performance practices.